2001
DOI: 10.1164/ajrccm.164.2.2008119
|View full text |Cite
|
Sign up to set email alerts
|

Airway Constriction Pattern Is a Central Component of Asthma Severity

Abstract: Measurements of lung resistance and elastance (RL and EL) from 0.1 to 8 Hz reflect both the mean level and pattern of lung constriction. The goal of this study was to establish a relation between a deep inspiration (DI) and the heterogeneity of constriction in healthy versus asthmatic subjects. Constriction pattern was assessed from measurements of the RL and EL from 0.1 to 8 Hz in seven healthy subjects and in 12 asthmatics. These data were acquired before and after a DI and before and after a standard methac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
131
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(147 citation statements)
references
References 32 publications
16
131
0
Order By: Relevance
“…The increases in the values of Edyn,rs9.25Hz/Edyn,rs0.5Hz and Edyn,rs19.75Hz/Edyn,rs0.5Hz likely reflected the effects of parallel time-constant mechanical heterogeneity (21) and airway shunt associated with severe narrowing and/or closure of peripheral airways (16), respectively. It is remarkable that the Rrs and Edyn,rs spectra obtained during the second phase of induced constriction in the murine model of asthma were similar to those reported in clinically stable asthmatic subjects (11,12) and in subjects with mild or moderately severe asthma during induced constriction (15). Recently, Tomioka et al (28) have investigated the pulmonary mechanical responses to methacholine in mice by using both the forced oscillation technique and the alveolar capsule technique.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The increases in the values of Edyn,rs9.25Hz/Edyn,rs0.5Hz and Edyn,rs19.75Hz/Edyn,rs0.5Hz likely reflected the effects of parallel time-constant mechanical heterogeneity (21) and airway shunt associated with severe narrowing and/or closure of peripheral airways (16), respectively. It is remarkable that the Rrs and Edyn,rs spectra obtained during the second phase of induced constriction in the murine model of asthma were similar to those reported in clinically stable asthmatic subjects (11,12) and in subjects with mild or moderately severe asthma during induced constriction (15). Recently, Tomioka et al (28) have investigated the pulmonary mechanical responses to methacholine in mice by using both the forced oscillation technique and the alveolar capsule technique.…”
Section: Discussionsupporting
confidence: 55%
“…In contrast, heterogeneous airway narrowing is associated with increases of RL at physiological breathing rates that exceed those of RL at high frequencies (5, 14). Furthermore, a large variability in the reduction of airway caliber is more likely to produce closure of airways, which enhances the magnitude of dynamic lung elastance (Edyn,L) and may impair gas exchange.Pulmonary resistance and Edyn,L spectra obtained in subjects with severe asthma during periods of clinical stability and in subjects with mild or moderately severe asthma during agonist-induced constriction are consistent with a pattern of severe and heterogeneous airway constriction and closure of airways (11,12,15). These manifestations of airway dysfunction are of paramount clinical importance because marked elevations of RL and Edyn,L at physiological breathing rates may lead to respiratory failure and eventually death.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…Intermittent deep inspirations dilate the airways and decrease hyperresponsiveness of the airways, but may also lead to bronchoconstriction in more severe asthma (Fish, Ankin, Kelly, et al, 1981;Lutchen, Jensen, Atileh, et al, 2001). In our study, three patients with high initial pCO 2 levels showed only small increases from pre-treatment (39.0 ± 1.1 mmHg) to post-treatment (39.6 ± 3.1 mmHg) and follow-up (41.6 ± 1.9 mmHg), and further qualitative inspection of their means in outcome variables suggested lower initial symptom scores (1.1 ± 0.3 vs. 1.5 ± 0.6) and PEF variability (13.2 ± 6.7 vs. 32.9 ± 14.5 %), combined with smaller reductions across training than in the 5 patients starting with lower pCO 2 levels (31.7 ± 2.4 mmHg).…”
Section: Pco2 Biofeedback In Asthma 18mentioning
confidence: 99%